Synodontis eupterus Larvae Masculinization Using Javanese Long Pepper Extract (Piper retrofractum) - Prassetyo Dwi Dhany Wijaya; Muhammad Zairin Junior; Dinar Tri Soelistyowati; Widanarni Widanarni (Journal Omni-Akuatika, 2017)
Synodontis eupterus male represents only 5-10 % of farmer total synodontis production, which limits male availability for reproduction purpose. A method widely used in overcoming the low male production was masculinization through synthetic hormones, which was restricted due to its adverse impact on the environment. Natural ingredients from plant were demonstrated in various studies to substitute the 17α-methyltestosteron hormone on masculinization. This research aimed at evaluating the effects of Javanese long pepper extract (JLP) through immersion on synodontis fish larvae. The research was conducted using factorial design with two faktor (4x2) consisted of eight treatments: 17α-methyltestosteron 2 mg L-1 (MT) immersion for 5 and 10 hours, JLP dose 0.125 mg L-1 (P1) immersion for 5 and 10 hours and dose 0.25 mg L-1 (P2) immersion for 5 and 10 hours compared to the control treatment without immersion (P0). A hundred of synodontis larvae of 10 days old after hatching each replication were used in the immersion treatments. The results showed that JLP treatments produced 25-40 % of male synodontis age four months, 1-2 % females and above 60 % intersex. While at age five months, the percentage of intersex fish decreased to 20-40 %, the female fish increased to  60-62 %, and male fish ranged 20-35 % in JLP compared to the control P0 (15 %). The dose of JLP 0.25 mg L-1 increased mortality of about 14-54 %.